A New Ultra Fast Conduction Mechanism in Insulating Polymer Nanocomposites - M. Xu; G. C. Montanari; D. Fabiani; L. A. Dissado; A. Krivda (Journal of Nanotechnology)
A brand new phenomenon, namely, electrical conduction via soliton-like ultra fast space charge pulses, recently identified in unfilled cross-linked polyethylene, is shown for the first time to occur in insulating polymer nanocomposites and its characteristics correlated with the electromechanical properties of nanostructured materials. These charge pulses are observed to cross the insulation under low electrical field in epoxy-based nanocomposites containing nanosilica particles with relative weights of 1%, 5%, 10%, and 20% at speeds orders of magnitude higher than those expected for carriers in insulating polymers. The characteristics of mobility, magnitude and repetition rate for both positive and negative charge pulses are studied in relation to nanofiller concentration. The results show that the ultra fast charge pulses (packets) are affected significantly by the concentration of nanoparticles. An explanation is presented in terms of a new conduction mechanism where the mechanical properties of the polymer and movement of polymer chains play an important role in the injection and transport of charge in the form of pulses. Here, the charge transport is not controlled by traps. Instead, it is driven by the contribution of polarization and the resultant electromechanical compression, which is substantially affected by the introduction of nanoparticles into the base polymer.